Peripheral internationalization at a crossroads: travelling, publishing and careers - Klein, Stefan; Monteiro de Castro Nascimento, Carolina (Serendipities. Journal for the Sociology and History of the Social Sciences, 2024)
The present article examines internationalization in a peripheral academic context by looking at graduate Sociology professors in Brazil. We focus foremost on research stays abroad and foreign publications, using mostly descriptive statistics. We aim to understand the elements that structure the choice of destination, how they express center-periphery dynamics, and their relation to a research grant called Bolsa Produtividade. Engaging in the debate with the literature on centers and peripheries, especially with the understanding that these are relational and condition each other, we observe the various dimensions and how internationalization strategies are presented. We distinguish between more or less prestigious graduate programs while comparing how they overlap with Brazilian regional inequalities. This sheds light on the pitfalls of the rising pressure to internationalize, and how it takes shape in the recent context.